Cortisol responses after a high intensity exercise protocol in adolescent swimmers - Moustogiannis, A.; Philippou, A.; Tampaki, M.; Kollias, L.; Papadopetraki, A.; Maridaki, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Steroid hormones play a key role in modulating the exercise training responses. In particular, cortisol can negatively affect athletic performance, potentially causing fatigue and inflammation, and high levels of this hormone have been associated with impaired performance in elite athletes (Crewther et al., 2011). However, little is known about the cortisol responses in adolescent swimmers after high intensity exercise. The purpose of this study was to determine the salivary cortisol levels in response to a high intensity exercise protocol in adolescent swimmers. Methods: Twelve adolescent swimmers (5 female, 7 male, age: 14.4±1.0 Tanner stage 4) participated in the study. Participants performed a high intensity swimming protocol, i.e. 3X200m front crawl at 90% of their best time and the time needed to complete each of the three 200m swimming distance (S1, S2, S3) was recorded. Swimmers were provided with salivate swabs to collect unstimulated mixed saliva before and immediately after the exercise protocol. The swab was placed in the mouth for one minute, then it was transferred into plastic tubes, centrifuged and the resulted saliva sample was analysed. Saliva samples were assayed in duplicate using a commercially available ELISA kit. Differences between the cortisol levels before and after the exercise protocol were analyzed using student`s T-test, while one-way ANOVA for repeated measures and Tukey`s post hoc tests were used for analyzing swimming performance. Pearson correlation coefficient (r) was used to reveal potential relationship between cortisol levels and swimming performance. Results are presented as mean ± SD. Results: Salivary cortisol was significantly higher (1407.4±740,2 pg/ml vs. 4435,9±3039,5 pg/ml p=0,004) after the high intensity protocol. Swimming performance, i.e. the time needed to complete the swimming distance, changed significantly from the first (S1) to the last 200m (S3) (S1: 2,20±0,08 vs. S2: 2,22±0,08 vs. S3: 2,25±0,08 p<0,05). A positive correlation was found between the S3 time and salivary cortisol levels, which marginally failed to reach statistical significance (p<0.05). Conclusion: The findings of the present study suggest a significant effect of the exercise protocol on the saliva cortisol levels in adolescents. The relationship found between the increased cortisol levels and decreased performance may imply a causative association of this hormone with the swimming performance that could moderate effectiveness and long term adaptations of training.